Digital blackout of Spanish scientific production in Google Scholar - Delgado-López-Cózar, Emilio; Martín-Martín, Alberto (Anuario ThinkEPI, 2018)
In the most recent edition of Google Scholar Metrics (2012-2016) there was an abrupt drop in the number of Spanish scientific journals; the total was 1,101 in the 2011-2015 edition but fell to 599 in the 2012-2016 edition. We conducted an analysis by discipline in order to find which journals were affected. After considering several hypotheses to explain this phenomenon, we conclude the main cause was the sudden disappearance of the Spanish bibliographic database Dialnet from Google Scholar. Because Dialnet is the only online source that provides information about an important number of Spanish journals (which do not have any other online exposure), being dropped by Google Scholar meant that all these Spanish journals, which had previously been indexed in Google Scholar Metrics, became suddenly invisible.